Penguatan Identitas Budaya Siswa Melalui Program Kamis Beradat Di SMAN 14 Bandar Lampung - Rizky Wahyudi; Anis Sri Wijayanti; Femas Erlangga Dwi Saputra; Raden Muhammad Setiawan; Abdul Halim; Hasan Hariri (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2026)
The Kamis Beradat Program is a policy initiated by the Government of Lampung Province aimed at preserving local language and culture through the habitual use of the Lampung language and traditional Lampung batik in educational and governmental institutions. This study aims to analyze the implementation of the Kamis Beradat Program at SMAN 14 Bandar Lampung, identify the challenges encountered, and formulate strategic solutions to enhance its effectiveness. The research employed a qualitative approach using a descriptive method. Data were collected through observations of the program's implementation within the school environment. The findings indicate that the implementation of the program, particularly in the use of Lampung batik, has been successful and has gained a high level of participation from the school community. To address the challenges related to the use of the Lampung language, sustainable strategies are needed, including strengthening the school's cultural environment, encouraging the use of the Lampung language in learning activities, establishing an appreciation system for students, and utilizing digital media as a means of cultural promotion.